Titanium imido complexes with tetraaza macrocyclic ligands - Swallow, D; McInnes, J; Mountford, P (1998)
Tetraaza macrocycle-supported tert-bulyl titanium imido complexes [Ti(NBut)(Mentaa)] (n = 4 2 or 8 3; H2Mentaa = 6,8,15,17-tetra- or 2,3,6,8,11,12,17,18-octa-methyl-5,14-dihydrodibenzo[b,i][1,4,8,11] tetraazacyclotetradecine, respectively), [Ti(NBut)(Me4taen)] (5, H2Me4taen = 5,7,12,14-tetramethyl-1,4,8,11-tetraazacyclotetradeca-4,6,11,13-tetraene) and [Ti(NBut)(TTP)] (6, H2TTP = 5,10,15,20-tetratolylporphyrin) together with the N2O2-donor Schiff base analogue [Ti(NBut)(acen)] (7, H2acen = 4,9-dimethyl-5,8-diazadodeca-3,9-diene-2,11-dione) were prepared in good yield from the readily available [Ti(NBut)Cl2(py)3] and the dilithium or disodium salts of the tetradentate ligands. The Ti=NBut groups in 2 and 3 underwent imido group exchange reactions with anilines to form [Ti(NR)(Mentaa)] (n = 4, R = C6H3Me2-2,6 4, Ph, C6H4(NO2)-4, C6H4(NMe2)-4; n = 4 or 8, R = C6H4Me-4), and with H2E (E = O or S) to give the oxo and sulfido analogues [Ti(E)(Me4taa)]. Compound 4 was also prepared in good yield from [Ti(NC6H3Me2-2,6)Cl2(py) 3] and Li2[Me4taa]. Reaction of 2 with 2 or 1 equivalents of ROH (R = Me or C6H3Me2-2,6) or pinacol afforded [Ti(OR)2(Me4taa)] and [Ti{OC(Me)2C(Me)2O}(Me4taa)] respectively. The crystal structures of 3 and 4 have been described.